Epidemic of Non-Communicable Diseases and Its Control - Bhattarai, MD (Kathmandu University Medical Journal, 2013)
Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 1-3 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7333